KINERJA KEUANGAN BANK PEMBIAYAAN RAKYAT SYARIAH MELALUI PENDEKATAN MAQASID SYARIAH INDEX (MSI) DAN PROFITABILITAS - Batin, Mail Hilian (Nurani, 2017)
This research aims to find out the performance condition of Islamic Rural Bank in Indonesia using the ranking system. This system seems to any bank that has the highest and lowest rank. This system can be observed with Maqasid Syariah or by seeing the profitability ratio. After we can discover the ranking , we move forward to analyze it using the two observation method called the Four Quadrant Kartesius Diagram. This research used a secondary data from quarterly financial report from March 2013 until December 2015. Based on the test result, when using Maqasid Syariah Index (MSI), there is difference between the first ranks and otherwise placed. While when using Comparative Performance Index (CPI), one of ranked firstwhile other at the lowest rank.